Pengaruh Pemberian Penguatan Pembelajaran Guru Terhadap Hasil Belajar Siswa Kelas IV MIS Ujung Batu - Era Mutiah; Emrida Harahap; Harahap, Nurhalimah (Journal Education Innovation (JEI), 2025)
Education is a fundamental component of national development, shaping a generation that is skilled and competent. The objective of this research was to evaluate the impact of reinforcement strategies on the academic outcomes of fourth graders at MIS Ujung Batu. It adopted a quantitative methodology, implementing a pre-experimental model that included both pre-test and post-test for a single group. The participants were 30 fourth-grade students from MIS Ujung Batu in Sosa District, Padang Lawas Regency, comprising 13 males and 17 females. Data were gathered through observation, surveys, and documentation. Descriptive statistical analysis revealed that the average pre-test score was 57.5, which increased to an average post-test score of 81.3. The hypothesis testing yielded a T-value of 5.22. At a 5% significance level (0.05), with degrees of freedom (df) = N-2 = 28, the critical T-value is 1.70. Since the calculated T-value exceeds the critical value (5.22 > 1.70), the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Research on hypothesis testing indicates that the application of verbal and tactile activities as forms of reinforcement positively influences student learning outcomes. These results underscore the significance of reinforcement in enhancing student engagement and academic performance. Consequently, educators are advised to employ consistent reinforcement techniques to elevate the standard of instruction within the classroom.